Speech recognition thresholds correlate with tinnitus intensity in individuals with primary subjective tinnitus - Mavrogeni, Panayiota; Maihoub, Stefani; Molnár, András (Frontiers in Neurology, 2025)
ObjectivesThis study aimed to analyze the relationship between tinnitus and speech audiometry results.Materials and methodsIn this investigation, 314 patients with primary subjective tinnitus and 279 patients with sensorineural hearing loss, serving as a control group, were enrolled. All participants underwent comprehensive assessments, which included pure-tone and speech audiometry.ResultsIn considering basic parameters, a slight predominance of females was noted in both groups, with left-sided and bilateral tinnitus being the most common types. There were no significant differences in pure-tone averages between the tinnitus and control groups. In the tinnitus group, speech audiometry intensity were significantly higher (p < 0.00001) compared to the control group. In analyzing the relationships between tinnitus intensities and speech audiometry intensity, a significant (p = 0.000) positive correlation (rho = 0.581) was revealed. Additionally, a significant (p = 0.027) positive correlation (rho = 0.227) was found between tinnitus intensities and Tinnitus Handicap Inventory scores.ConclusionThe relationship between tinnitus intensities and speech audiometry intensity demonstrates how tinnitus affects speech comprehension. Additionally, the intensity of tinnitus significantly influences an individual’s perception of tinnitus severity.